Fast XANES fluorescence imaging using a Maia detector. (25th April 2018) - Boesenberg, Ulrike; Ryan, Christopher G.; Kirkham, Robin; Jahn, Andreas; Madsen, Anders; Moorhead, Gareth; Falkenberg, Gerald; Garrevoet, Jan
Abstract : The evaluation of a new fast XANES scanning scheme in fluorescence mode for spectromicroscopy using a Maia detector with high spatial and spectral resolution at the P06 beamline, DESY, is presented. Abstract : A new fast X‐ray absorption spectroscopy scanning method was recently implemented at the Hard X‐ray Microprobe endstation P06, PETRA III, DESY, utilizing a Maia detector. Spectromicroscopy maps were acquired with spectra for X‐ray absorption near‐edge structure (XANES) acquisition in the sub‐second regime. The method combines XANES measurements with raster‐scanning of the sample through the focused beam. The order of the scanning sequence of the axes, one beam energy axis and two (or more) spatial axes, is a variable experimental parameter and, depending on it, the dwell at each location can be either single and continuous (if the energy axis is the inner loop) or in shorter discontinuous intervals (if a spatial axis is innermost). The combination of improved spatial and temporal resolution may be necessary for rapidly changing samples, e.g. for following in operando chemical reactions or samples highly susceptible to beam damage where the rapid collection of single XANES spectra avoids issues with the emergence of chemical changes developing from latent damage. This paper compares data sets collected on a specially designed test pattern and a geological thin‐section scanning the energy as inner, middle and outer axis in the sequence. The XANES data of all three scanning schemes is found to show excellent agreement down to the single‐pixel level.